2006
DOI: 10.1111/j.1471-4159.2006.03649.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol inhibits L1 cell adhesion molecule activation of mitogen‐activated protein kinases

Abstract: Inhibition of the functions of L1 cell adhesion molecule (L1) by ethanol has been implicated in the pathogenesis of the neurodevelopmental aspects of the fetal alcohol syndrome (FAS). Ethanol at pharmacological concentrations has been shown to inhibit L1-mediated neurite outgrowth of rat post-natal day 6 cerebellar granule cells (CGN). Extracellular signal-related kinases (ERK) 1/2 activation occurs following L1 clustering. Reduction in phosphoERK1/2 by inhibition of mitogen-activated protein kinase kinase (ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 61 publications
(158 reference statements)
3
57
0
Order By: Relevance
“…The mAbs to L1 could drastically reduce Erk and Src activation. It is interesting to note that in neuronal cells, L1 crosslinking with antibodies led to Erk activation (Schaefer et al, 1999;Tang et al, 2006), whereas in carcinoma cells the opposite is observed. In SKOV3ip cells that were used before as a therapy model in nude mice (Arlt et al, 2006;Knogler et al, 2007), the treatment with L1-mAbs was accompanied by changes in the expression pattern of Erk-regulated genes.…”
Section: Discussionmentioning
confidence: 97%
“…The mAbs to L1 could drastically reduce Erk and Src activation. It is interesting to note that in neuronal cells, L1 crosslinking with antibodies led to Erk activation (Schaefer et al, 1999;Tang et al, 2006), whereas in carcinoma cells the opposite is observed. In SKOV3ip cells that were used before as a therapy model in nude mice (Arlt et al, 2006;Knogler et al, 2007), the treatment with L1-mAbs was accompanied by changes in the expression pattern of Erk-regulated genes.…”
Section: Discussionmentioning
confidence: 97%
“…The reduction of MAPK/Erk activity may be involved in the alcohol-induced impairment of granule cell migration. This is because the reduction of phosphorylated Erk1 and Erk2 by inhibition of MAPK kinase inhibits neurite outgrowth in cerebellar granule cells [138] . Moreover, PKC and PKA alter the phosphorylation of Erk [139] .…”
Section: Future Work To Further Understand Neuronal Migration In Fasmentioning
confidence: 99%
“…In addition, ethanol has been shown to affect, e.g., several signal transduction pathways (218,219,220), neuronal adhesion molecules (221,222), and extracellular matrix proteins (171), which may contribute to the ethanol-induced pathology of the developing, mature and/or aging cerebellum. Several important questions, however, remain to be answered in future studies on ethanol-induced cerebellar degeneration: (i) What is the relative impact of each of the described mechanisms in the cerebellum vs. in other CNS areas sensitive to ethanol-induced pathology (e.g., frontal cortex, hippocampus, basal cholinergic neurons)?…”
Section: Discussionmentioning
confidence: 99%